Borophosphosilicate glass component analysis using secondary neutral mass spectrometry - Oberemok, O.; Lytvyn, P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
In the present study the SNMS technique for the quantitative component analysis of the borophosphosilicate glass layers was used. These layers were deposited on the silicon substrate by chemical vapor deposition method. The charge-up of the surface is compensated by plasma gas electrons in the high frequency mode sputtering. It is shown that modes of such sputtering significantly influence on the macro- and microrelief of the crater during the process of the depth component distribution analysis. An on-off time ratio change of the voltage applied to the sample results in changing the crater shape. At the same time the increase of the sputtering frequency results in appearance of thin protrusions at the crater bottom. Improvement of the depth resolution requires optimization both on-off time ratio and frequency of voltage applied to the sample.